Richard Pring Keynote: Educational Philosophy of John Dewey and it's relevance to current dilemmas in Education - Richard Pring (University of Aberdeen, School of Education, 2017)
This paper was originally given as a Keynote address at Democracy and Education International Conference, 15th June 2016, University of the West of Scotland, Ayr Campus, Scotland.